2014
DOI: 10.1016/j.jimonfin.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The cost of private debt over the credit cycle

Abstract: This Working Paper should not be reported as representing the views of the IMF. The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate. We identify global and regional fluctuations in international private debt flows to emerging and developing countries using data on cross border loans and international bond issua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Third, our study contributes to the recent studies on the determinants of bank loan contracting, including shareholder rights (Chava et al., 2008), corporate misreporting (Graham et al., 2008), private sector share of external debt (Hallak, 2013), cost of private debt (Francis et al., 2014), political connections (Houston et al., 2014), tax evasion (Hasan et al., 2014), private information (Carrizosa & Ryan, 2017), social capital (Hasan et al., 2017) and intellectual property rights (Alimov, 2019). We complement this line of research by showing that perceived board corruption has a significant impact on loan contracts.…”
Section: Introductionmentioning
confidence: 71%
“…Third, our study contributes to the recent studies on the determinants of bank loan contracting, including shareholder rights (Chava et al., 2008), corporate misreporting (Graham et al., 2008), private sector share of external debt (Hallak, 2013), cost of private debt (Francis et al., 2014), political connections (Houston et al., 2014), tax evasion (Hasan et al., 2014), private information (Carrizosa & Ryan, 2017), social capital (Hasan et al., 2017) and intellectual property rights (Alimov, 2019). We complement this line of research by showing that perceived board corruption has a significant impact on loan contracts.…”
Section: Introductionmentioning
confidence: 71%
“…It is precisely because the interest rate is higher that the supply of credit by bond investors increases when the supply of credit by banks declines. A detailed analysis of the behavior of interest rates for various debt instruments is beyond the scope of this paper due to the lack of comparable series between instruments and economies in our panel data -see Francis et al (2014) for such analysis using micro-level data. Therefore, we focused on the credit quantities in our empirical analysis.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…3 However, as discussed in more detail below, the experience has shown that the notion of bond markets as "spare tires" may not hold under sufficiently severe disruptions. 4 Cross-border syndicated lending and international private bond issuances, on the other hand, historically show cyclical variation in volumes and interest rates spreads (Francis et al, 2014). The present EM corporate bond boom thus can be in part driven by the temporary easing of financial conditions in global markets.…”
Section: Introductionmentioning
confidence: 99%